Spatial panel analysis on ASEAN–China trade links - Yong, Chen Chen; Yew, Siew Yong; Chin, Mui Yin (World Scientific Publishing, 2019)
The change of trade structures from the dynamic development of production networks globally had caused processing trade to become more prominent in China. This change drives ASEAN5 to be more aggressive in developing vertical intra-industry trade (VIIT) with China. This study aims to identify the catalysts that strengthened the VIIT relationship between ASEAN5 and China for manufacturing sub-sectors. Both decomposition-type threshold method and spatial panel econometric modelling are used and the results show that foreign direct investment (FDI) and difference in gross domestic products (DGDP) are the influential determinants of VIIT although their impacts vary across manufacturing sub-sectors. The results also confirm the presence of spatial interaction effects among ASEAN5 countries in relation to China's trade. These suggest that deeper economic integration among ASEAN5 countries is vital in strengthening bilateral VIIT with China. Moreover, to foster the value chain between the two regions, emphasis on performing similar tasks with differentiated varieties of products is essential as the two regions have similar comparative advantages.